Eksistensi Tradisi Tahlilan di Tengah Arus Modernisasi Di Dukuh Kalipucang Desa Kedungbanteng - Ulil Amri; Nafiah Nafiah; Wahyudi Wahyudi (Social Science Academic, 2025)
The aim of this study is to explore and understand how the tradition of tahlilan can persist and adapt amidst the rapid pace of modernization. This research employs a qualitative descriptive approach, utilizing interviews as the primary data collection method to explore how the tahlilan tradition is maintained in the context of modernization. The objective is to understand the significance and evolution of tahlilan practices within the community of Dukuh Kalipucang, Kelurahan Kedungbanteng. The results indicate that values such as charity, mutual aid, and maintaining social connections remain integral to the practice of tahlilan. The tradition plays a crucial role in strengthening community bonds through religious gatherings and assemblies, thus enhancing community knowledge and ensuring the preservation of the tradition. The conclusion of this research is that, despite facing challenges from modernization, the tradition of tahlilan retains a significant place within the community. The adaptations made demonstrate that the tradition serves as a bridge between traditional values and modern demands, reinforcing community identity while simultaneously adapting to social and cultural developments.